The Effect of Cake Application Toward Students Speaking Mastery (A Quasi Experimental at the Tenth Grade Students of SMAN 04 Seluma Academic Year 2024-2025) - Elpita Sari; Ferri Susanto; Yashori Revola (The Future of Education Journal, 2026)
Research this study aimed to investigate the effect of 1using the Cake application on students’ English speaking ability at Grade X of SMA Negeri 04 Seluma in the academic year 2024/2025. Previous studies have reported that mobile-assisted language learning applications contribute positively to vocabulary mastery and listening skills; however, empirical evidence focusing specifically on speaking ability at the senior high school level, particularly in rural school contexts, remains limited. To address this gap, this research employed a quantitative approach using a quasi-experimental design involving two groups: an experimental group taught using the Cake application and a control group taught using conventional teaching methods. The research instrument was a speaking test consisting of 17 incomplete-sentence items administered at the pre-test and post-test stages. The instrument was tested and confirmed to be valid and reliable. The findings showed that the mean post-test score of the experimental group (74.79) was higher than that of the control group (62.23). Statistical analysis using a paired sample t-test indicated a significant difference between the two groups (0.000 < 0.05). These results indicate that the use of the Cake application is effective in improving students’ English speaking ability. Therefore, integrating mobile learning applications such as Cake can be considered a viable instructional strategy to enhance speaking skills in English language learning at the senior high school level.